Técnicas de tinciones especiales para el estudio de patologías en tejidos humanos - Joselyn Lisseth, Barragan Lizano (2021)
ABSTRACT A special staining makes it possible to reveal biological structures present in the histological sections, which are difficult to identify with the routine ones. The objective of the research project was to collect information on the use of special stains for the diagnosis of pathologies in human tissue. This research carried out under a descriptive-level documentary-bibliographic design. From a population of 80 bibliographic sources, for the development, inclusion and exclusion criteria applied taking 53, updated, reviewed and verified by researchers who approve their publication, in which they were repositories, books and scientific databases, highlighting its scarce information, it was possible to obtain reliable sources. Stains that study specific structures such as Congo Red found to stain amyloid, expressing greater sensitivity to its protein structure, the uptake of ferric ion for melanin in case of emergency, but it left to the consideration of the corresponding personnel since Fontana de Masson uses more time, but allows more intensity when identifying it. Grocott is more sensitive for fungi, although it has a high cost, but PAS that in the same way allows its identification, but with less sensitivity, Ziehl Neelsen for acid-resistant bacteria, Alcian Blue and PAS allow the observation of carbohydrates and mucins that contain deposits. of heparan sulfate and dermatan sulfate that can cause neurological damage, cardiomyopathies, including for mucinous adenocarcinoma of the ovary, pleural mesothelial cell, myxomas, in discoid lupus erythematosus lesion and mucinous materials in myxedema. Key words: Special stains, pathological tissue. Reviewed by: Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324